Phase-field crystal study on the influence of nanoscale intergranular structures on grain boundary segregation. (27th October 2021) - Su, Shasha; Tang, Sai; Liang, Chaoping; Ma, Yunzhu; Liu, Wensheng
Abstract: Grain boundary (GB) segregation can substantially affect the performance of materials by greatly changing the chemical compositions of GB. It is well known that GB segregation is essentially attributed to the structural differences between the bulk of grain and GB. Nevertheless, we still lack a clear understanding about the correlation between nanoscale intergranular structures and solute segregation. In this work, by using the phase-field crystal model, we performed atomic scale simulations to investigate the segregation of Li atoms to symmetric ⟨110⟩ tilt GBs in binary Al–Li alloys. It was found that the amount of segregated solute increases proportionally to GB misorientation angle in the case of low-angle tilt GBs, and converges at high-angle tilt GBs, except some special GBs with coincidence-site lattice. This is analogous to the dependences of GB energy and density on the misorientation angle. The correlations among GB structure, misfit strain around GBs and solute segregation are quantified at atomic scale. In low-angle tilt GBs, Li atoms are segregated to the compress zone around the core of intergranular dislocations to release the misfit strain energy. In the general high-angle tilt GBs, since the GB structure and misfit strain energy is uniform, the segregated atoms distribute homogeneously along GB. Particularly, the regular arrangement of structural units in some low Σ GBs lead to very low misfit strain energy, and accordingly to a periodically distributed and very low amount of solute segregation.